Isolated cardiac hydatid cyst of the right ventricle: Cardiac hydatid cyst - Ozdemir , Ahmet Coskun; Akdogan , Ali; Guven , Kibar Yasar (Journal of Surgery and Medicine, 2022)
A hydatid cyst is a parasitic disease that most commonly affects the liver and lungs: it rarely affects the heart: right ventricular involvement is even less common. A 33-year-old male patient with a cardiac cystic mass, detected during echocardiography, was evaluated. Early surgery was the best treatment option. A hydatid cyst is located in the right ventricular wall and detected during surgery. The cyst was drained and the defect in the right ventricle was quilted. Postoperative follow-ups occurred, and he was discharged with albendazole in good health.